Proses Belajar dalam Perspektif Psikologi Pendidikan - Abu Husein Ibrahim Al 'ithriy; Siti Rohimah (TSAQOFAH, 2026)
The learning process is the core of education because it plays a role in shaping changes in learners’ behavior through experience, practice, and interaction with the environment. This study aims to examine the essence of the learning process from the perspective of educational psychology, its dimensions, the factors that influence learning success, and its implications for educational practice. This study uses a library research method with a qualitative descriptive approach. Data were obtained from various relevant literature, including books, scientific journals, and articles, and were then analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings show that the learning process produces relatively permanent behavioral changes in cognitive, affective, and psychomotor aspects. Learning success is influenced by internal factors, such as motivation, interest, and learning readiness, as well as external factors, such as the learning environment, instructional methods, and the role of teachers. In addition, the integration of spiritual values and the appropriate use of technology can support the improvement of learning quality. The conclusion of this study affirms that the learning process needs to be understood as a multidimensional activity that emphasizes not only the mastery of knowledge but also the formation of attitudes, skills, and values. The implications of this study indicate the importance of a holistic learning design that is learner-centered, adaptive to technological developments, and aligned with the values of Islamic education.